Learning from Other Religious Traditions Leaving Room for Holy Envy (Pathways for Ecumenical and Interreligious Dialogue, 2018)
This book brings together academic scholars from across various religious traditions to reflect on the beauty they find in traditions other than their own. They examine these aspects and reflect on how they inform and constructively assist with rethinking their own religious worldviews and practices. Each scholar investigates the various implications, questions, insights, and challenges that are generated in the process of doing so. Traditions discussed include Ásatrú Heathenism, Buddhism, Catholicism, Evangelical Christianity, Hinduism, Islam, Judaism, LDS Mormon Christianity, Lutheranism, Presbyterianism, Sikhism, Sufism, Western Buddhism, and Zen Mahāyāna Buddhism. Instead of focusing only or primarily on the theory and practice of interreligious dialogue, this book presents living examples of learning from other religious traditions, identities, and persons. .